Studying for Your Nursing Degree - Bottomley, Jane; Pryjmachuk, Steven (Critical Study Skills, 2017)
Studying for your Nursing Degree is PERFECT for anyone wanting to train to become a nurse or midwife. After reading this fully comprehensive guide you will understand: the structure and culture of higher education, and how nursing fits into it what to expect, and what will be expected of you, as a university student teaching and assessment methods within nursing, so that you can perform to the best of your ability in an academic environment how to manage your nursing studies in an effective way and make the most of the resources available to you. The books in our Critical Study Skills series will help you gain the knowledge, skills and strategies you need to achieve your goals. They provide support in all areas important for university study, including institutional and disciplinary policy and practice, self-management, and research and communication. Packed with tasks and activities to help you improve your learning, including learner autonomy and critical thinking, and to guide you towards reflective practice in your study and work life. Uniquely, this book is written by an experienced education lecturer and an English for Academic Purposes (EAP) lecturer.